The Government and capital formation - Von Furstenberg, George M. (Cambridge, Mass. : Ballinger Pub. Co., 1980)
The text probes the underlying causes and determinants of savings, investment, and economic growth and examines the ways in which government and other institutions affect capital formation.
Volume II in the series on Capital Investment and Saving sponsored by the American Council of Life Insurance
Includes bibliographies and index.
rpm 19/09/2017
Loans
Keywords: Saving and investment; Fiscal policy; Monetary policy; United States